2023
DOI: 10.1111/spc3.12770
|View full text |Cite
|
Sign up to set email alerts
|

Data absence and a lack of parsimony: A response to Kay and Arrow's elemental Dark Triad

Abstract: Arrow's (2022) recent Social and Personality Psychology Compass article, the same dubious attacks have also emerged elsewhere. We remind the field that although there are reasons to keep an eye on the overlap among the traits, the field of Dark Triad research is progressing well. Overwhelming evidence demonstrates that the traits are independent of one another-both theoretically and empirically. The bulk of concerns regarding Dark Triad overlap stem from Machiavellianism and psychopathy. However, it is critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Of the 10 studies reported by Jones and colleagues, only two statistically compared the associations. In those two cases, the associations for Machiavellianism and psychopathy were significantly different (although they were not, as argued by Andrews and colleagues (2023), opposite). We commend Jones and colleagues for testing these differences.…”
Section: Misconception 5: Correlations Do Not Need To Be Statisticall...mentioning
confidence: 69%
See 4 more Smart Citations
“…Of the 10 studies reported by Jones and colleagues, only two statistically compared the associations. In those two cases, the associations for Machiavellianism and psychopathy were significantly different (although they were not, as argued by Andrews and colleagues (2023), opposite). We commend Jones and colleagues for testing these differences.…”
Section: Misconception 5: Correlations Do Not Need To Be Statisticall...mentioning
confidence: 69%
“…In responding to our article, Andrews and colleagues (2023) also asserted that Machiavellianism and psychopathy are empirically distinct because they manifest in opposite relations with various criteria. In support of this claim, they cited seven articles, comprising 10 studies, from Jones and colleagues.…”
Section: Misconception 5: Correlations Do Not Need To Be Statisticall...mentioning
confidence: 85%
See 3 more Smart Citations